Impact of Turkish Policy Reform on Labor Force Status of Disabled Males: A Difference-in-Difference Analysis - Öncel, Burcu Düzgün; Karaoğlan, Deniz (Panoeconomicus, 2022)
This paper aims to study the effect of a Turkish policy reform enacted in 2008 that requires firms to hire disabled applicants. Our attention is only on males to avoid complications arising from gender differences in disability and labor force participation. The data is from the Turkey Health Survey (THS) of the Turkish Statistical Institute (TurkStat) for the years 2008 and 2012. We define “disability” as an impairment of long-term health conditions that lasts more than six months and that restricts the individual in daily activities. We use difference-in-difference (DD) estimation, in which the DD estimator is the difference between disabled and non-disabled individuals in the difference in labor force participation before and after the new policy. The results suggest an insignificant effect of the treatment on the treated, implying that the policy reform does not create any incentive for disabled males to participate in the labor force. Keywords: Disability, Labor force participation, Difference-in-difference. JEL: I12, J21, J24, C31, C34.